Fuzzy logic based power management strategy using topographic data for an electric vehicle with a battery-ultracapacitor energy storage. Issue 1 (5th January 2015) - Michalczuk, Marek; Ufnalski, Bartlomiej; Grzesiak, Lech M.
Abstract : Purpose: – The purpose of this paper is to provide high-efficiency and high-power hybrid energy source for an urban electric vehicle. A power management strategy based on fuzzy logic has been introduced for battery-ultracapacitor (UC) energy storage. Design/methodology/approach: – The paper describes the design and construction of on-board hybrid source. The proposed energy storage system consists of battery, UCs and two DC/DC interleaved converters interfacing both storages. A fuzzy-logic controller (FLC) for the hybrid energy source is developed and discussed. Control structure has been tested using a non-mobile experimental setup. Findings: – The hybrid energy storage ensures high-power ability. Flexibility and robustness offered by the FLC give an easy accessible method to provide a power management algorithm extended with additional input information from road infrastructure or other vehicles. In the presented research, it was examined that using information related to the topography of the road in the control structure helps to improve hybrid storage performance. Research limitations/implications: – The proposed control algorithm is about to be validated also in an experimental car. Originality/value: – Exploratory studies have been provided to investigate the benefits of energy storage hybridization for electric vehicle. Simulation and experimental results confirm that the combination of lithium batteries and UCs improves performance and reliability of the energy source. To reduce power impulses drawn from the battery, power management algorithm takes into consideration information on slope of a terrain.